MANAGEMENT STRESS OF STUDENT IN SOUTH SULAWESI DURING THE PANDEMIC COVID-19 - Fadly Umar; Yudi Adnan; Munadiah Wahyuddin; Anita Mariani; Tuti Alawiah; Irna Imran; Indah Cahyani (Homes Journal = Hospital Management Studies Journal, 2022)
The stipulation of COVID-19 as a global pandemic has made the Indonesian government make several strategic policies to avoid the transmission of this virus, one of which is online lectures. However, it cannot be denied that there are constraints faced by students such as non-existent networks, running out of internet packages, homework that must be done as well, and piling up lecture assignments cause them to experience stress. The purpose of this study was to determine the stress level of students during online lectures during the COVID-19 pandemic. This study uses a quantitative research with an observational analytic approach with a cross sectional study design. The population in this study were students from State Universities South Sulawesi. The sample in this study were 133 respondents using accidental sampling method. The results of statistical tests, that most of the respondents had a normal stress level (42.9%), age variable value p value = 0.301> 0.05, gender p value = 0.172> 0.05, institution origin p value = 0.367> 0.05, semester level p value = 0.474> 0.05, study program p value = 0.199> 0.05, and performance index p value = 0.075 concluded that all the independent variables are not related to student stress levels.